Synergetic effects of biochars and denitrifier on nitrate removal. (September 2021) - Liu, Yuqi; Liu, Shulei; Yang, Zongcai; Xiao, Lin
Graphical abstract: Highlights: Bacteria colonized on biochars despite of unfavorable interfacial interaction. Biochars with immobilized denitrifier improved nitrate removal efficiency. Denitrifier-immobilized biochar removed nitrate without lag time. Biochars stimulate bacterial growth, enzyme activity and ETSA. Synergetic interaction on nitrate removal exists between denitrifier and biochars. Abstract: Nitrate is one of the most common water contaminants and has caused severe environmental problems. This work aimed to investigate the effects of integration of denitrifier with biochars on nitrate removal and understand the underlying mechanisms. The results showed that physiochemical properties of biochars varied according to different feedstocks, which influenced bacteria attachment and nitrate removal through adsorption. However, bacteria could colonize on biochars no matter biochars surface were favorable for bacteria attachment or not. Immobilization of denitrifier on biochars significantly improved nitrate removal efficiencies and reduced lag time. Underlying mechanisms investigation showed that the integration of denitrifier with biochars had synergetic effects on promoting nitrate removal, which improved not only the expression and activity of nitrate reductase, but also the electron transport system activity.